ANTI-PATHOGENIC Candida Spp. Activity DETERMINATION VIA Lactobacillus Spp. ISOLATION AND IDENTIFICATIONS USING CONVENTIONAL AND MOLECULAR METHODS - Hawraa F. H. AL-abedi; Azhar A.F. AL-Attraqchi; Bassam Y. Khudaier (Basrah Journal of Veterinary Research)
Two Hundred and fifty samples of cow's milk from different parts of theprovince of Basrah were collected from clinical and subclinical mastitis reportedusing the California mastitis test between March 2018 and September 2019 andexamined using conventional PCR assay, Candida species was identified in 116/250(46.4%). Based on conventional method and ID - Yst card system Vitek 2, Candidaalbicans was the predominant 60/116 (51.7%), followed by Candida parapsilosis15/116 (12.9%). Concerning the results of PCR amplification of 18S rRNA gene foridentification of C. albicans and C. parapsilosis, this gene was present in 60 samplesin C. albicans, and in 15 of C. parapsilosis. Lactobacillus are an industriallyimportant group of probiotic organisms that play an important function in humanhealth through inhibiting dangerous and pathogenic bacteria growth, boostingimmune function, and increasing resistance to infection. Ten out of 250(4%)Lactobacillus isolates were obtained from apparently healthy cow milk samples.Lactobacillus isolates were identified according to phenotypic characterization andmolecular technique using PCR (16S rRNA) and sequencing, it was seen that L.acidophilus formed 5 isolates (50%), L.amylovorus was three (30%), while L.crisaptus formed only two (20%) only. The results of this study revealed that theBLAST analysis at the NCBI gene bank gave 99.39% homology with L. acidophilus,99.19% homology with L.crispatus and 97.59% with L. amylovorus. In vitroantimycotic activity of probiotic bacteria (Lactobacillus) against C. albicans and C.parapsilosis using agar well diffusion methods was adapted. The cell-free neutralizedsupernatant (CFS) of Lactobacilli (105,106,107) were inhibited the growth ofpathogenic C.albicans and C. parapsilosis. It was also noticed that, L. acidophilusshowed the strongest antifungal activities against pathogenic C. albicans andC.parapsilosis with different degrees of inhibition zones in comparsion with each ofL.crispatus and L. amylovorus, meanwhile, L. amylovorus revealed strongestantifungal activity against pathogenic C.parapsilosis.